Genome-wide analysis of the AP2/ERF gene family in Tritipyrum and the response of TtERF_B2-50 in salt-tolerance - Xiaojuan Liu; Guangyi Zhou; Songshu Chen; Zhenzhen Jia; Suqin Zhang; Mingjian Ren; Fang He (BMC Genomics, 2023)
Abstract The AP2/ERF transcription factor is widely distributed across the plant kingdom and plays a crucial role in various abiotic stress responses in plants. Tritipyrum, an octoploid resulting from an intergeneric cross between Triticum aestivum (AABBDD) and Thinopyrum elongatum (EE), is a valuable source of germplasm for incorporating superior traits of Th. elongatum into T. aestivum. With the recent availability of whole -genome sequences for T. aestivum and Th. elongatum, we explored the organization and expression profiling of Tritipyrum AP2/ERF genes across the entire genome. Our investigation identified 543 Tritipyrum AP2/ERF genes, which evolutionary analysis categorized into four major groups (AP2, DREB, ERF, and RAV), whose members share a conserved motif composition. These 543 TtAP2/ERF genes were distributed throughout 28 chromosomes, with 132 duplications. Synteny analysis suggests that the AP2/ERF gene family may have a common ancestor. Transcriptome data and Real-Time PCR expression profiles revealed 43 TtAP2/ERF genes with high expression levels in response to various salt stressors and recovery regimens. Tel2E01T236300 (TtERF_B2-50) was particularly salt stress-sensitive and evolutionarily related to the salt-tolerant gene AtERF7 in A. thaliana. Pearson correlation analysis identified 689 genes positively correlated (R > 0.9) with TtERF_B2-50 expression, enriched in metabolic activities, cellular processes, stimulus response, and biological regulation. Real-time PCR showed that TtERF_B2-50 was highly expressed in roots, stems, and leaves under salt stress. These findings suggest that TtERF_B2-50 may be associated with salt stress tolerance and may serve as a valuable foreign gene for enhancing salt tolerance in wheat.